TYROSINASE INHIBITION AND ANTI-OXIDANT PROPERTIES OF MUNTINGIA CALABURA EXTRACTS: IN VITRO STUDIES - K P BALAKRISHNAN; NITHYA NARAYANASWAMY; ARUN DURAISAMY (International Journal of Pharma and Bio Sciences, 2011)
The present investigation deals with identifying new potential skin-lightening and antioxidant agents from natural origin for treating the hyperpigmentation disorders. The medicinal plant, Muntingia calabura was selected as the candidate plant for the present study. 10 % (w/v) extract of various parts (leaf, flower and fruit) of M.calabura in different solvents (aqueous, ethanol, hydroethanol and petroleum ether) was prepared by decoction method. The antityrosinase activity of the extracts from various parts of the plant was determined by using mushroom tyrosinase as an apt model system and it was found that the hydroethanolic extract of leaves from M. calabura possessed the maximum tyrosinase inhibiting potential among the various parts examined. The antioxidant activity of leaf extract of the plant was also ascertained by using 2, 2-diphenyl 1-picryl hydrazyl (DPPH) scavenging assay and ferric thiocyanate assay. The results showed that DPPH scavenging activity of hydroethanolic extract of leaves was in a dose dependant manner with the IC50 value of 8.5 µg. The inhibition of lipid peroxidation was almost similar in aqueous and hydroethanolic leaf extracts of M.calabura. The phenolic content of various solvent extracts of M.calabura leaves was also determined. The hydroethanolic extract of M.calabura leaves exhibited the phenolic content to a greater extent. Our findings revealed that leaves of M.calabura exerted the potent antityrosinase and antioxidant activities.